Improving Mathematical Problem-Solving Ability through Project-Based Learning in Elementary Linear Algebra: A Study of Mathematics Education Students - Rosi, Rosi Widia Asiani; Susi, Susi Marisa; Indah, Indah Nurul Hazairin; Sherli, Sherli Permata; Cut, Cut Multahadah; Fitri, Yuliana Safitri (Universitas Negeri Padang, 2025)
Elementary Linear Algebra covers the study of matrices and vectors. One practical application of matrix concepts in daily life and technology is the Hill Cipher cryptosystem. Cryptography is the science of securing confidential messages, while the Hill Cipher is a cryptographic method that uses matrices in the encryption process. The Hill Cipher can be applied as a project in Project-Based Learning (PjBL) for the Elementary Linear Algebra course, particularly in the topic of matrices, with the aim of improving students’ problem-solving abilities. This approach serves as an alternative to the conventional learning methods commonly used. Through the implementation of PjBL, it is expected that the course learning outcomes can be achieved and that students will become more creative and innovative in solving problems. This study is a quantitative research with quasi experimental design conducted on third-semester students of the 2023/2024 academic year in the Mathematics Education (Tadris Matematika) program, Faculty of Tarbiyah and Teacher Training, UIN Sulthan Thaha Saifuddin Jambi. Observation sheets were used to examine the implementation of the PjBL model, including the alignment between the learning process and the syntax and principles of PjBL, as well as the effectiveness of the projects used. Tests were administered to measure students’ mathematical problem-solving ability after the implementation of the PjBL model, in the form of essay questions referring to indicators of mathematical problem-solving ability. The effect of the effectiveness of the PjBL implementation to improve students problem-solving ability was analyzed using the N-gain test on the results of the mathematical problem-solving ability test. The obtained N-gain score was 0.5786, which falls into the moderate category, indicating that the PjBL model is moderately effective to improve problem solving ability.